Optimization Method and Experimental Study on the Shear Strength of Externally Prestressed Concrete Beams. Issue 4 (April 2014) - Wang, Jingquan; Qi, Jianan; Zhang, Jian
This paper presents a performance-based evolutionary topology optimization method for externally prestressed concrete(EPC) beams in automatically generating optimal strut-and-tie models using the finite element method. The concrete and steel bar elements with least contribution to the stiffness of the EPC beam are removed by calculating the element virtual strain energy. Load transfer mechanism of EPC beam is characterized by remaining elements. The optimal strut-and-tie model is determined from the topology history. A theoretical formula of the shear strength is derived from optimal strut-and-tie model for EPC beams. The model predicts possible modes of failure, which may be broadly classified into shear-type failure and flexural-type failure. 9 EPC beams were casted in place to evaluate the validation of the proposed method. The predictions of the method are compared with the 9 specimen and other available test results of EPC beams from literatures. Case studies are conducted and compared with the results of the ACI 318–11 Code and AASHTO specification equations to evaluate the accuracy of the proposed method. It is shown that the proposed method can be used in practice, especially in the design of complex externally prestressed concrete members where no previous experience is available.